Pengaruh Model Pembelajaran Investigasi Kelompok berbantuan Perangkat Lunak Maple terhadap Kemampuan Pemecahan Masalah Matematis - Wulandari, Putri; Mujib, Mujib; Putra, Fredi Ganda (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to determine the effect of mathematical problem solving ability of learners who follow the learning by using an instructional model of maple assisted software assisted, with learners who use, study group investigation model, as well as learners who follow the conventional learning model conducted by researchers on participants Students of class X SMK Muhammadiyah 1 Metro. This type of research is a quasi experimental research with posttest only control design design. Hypothesis test using a one-way anava test with unequal cells and obtained the conclusion that the model of group investigation learning is better than an instructional model of maple assisted software group and both models of learning is better than conventional learning model. Based on the results of analysis and discussion of research data obtained that there is an influence on the ability of solving mathematical problems among students in class applying group investigation model assisted maple software, students in class apply only group investigation learning model, and students whose class apply the conventional learning model on the principal Discussion of the matrix.